2019
DOI: 10.1177/1039856218822743
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of postpartum psychosis in a mother-baby unit: do both mother and baby benefit?

Abstract: Objectives: To describe characteristics and treatments of mother-baby dyads affected by postpartum psychosis admitted to a specialist mother-baby inpatient psychiatric unit in Australia. Methods: A retrospective review of medical records for all mothers with postpartum psychosis and their babies admitted to a mother-baby unit over a 5-year period was conducted. Results: A total of 25 dyads met the study criteria. Affected women were found to be severely ill with a high rate of involuntary status (64%). They wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The findings reveal contact with healthcare services is inconsistent and can even hinder accessing support, suggesting that NICE guidelines are not being consistently met. This may reflect differences in service provision, including insufficient availability of specialist MBUs which can result in delays receiving appropriate help (Hill et al 2019 ; Jones and Smith 2009 ). It was also found that the needs as a family were often not adequately addressed, echoing work in the broader area of maternal mental health (Megnin-Viggars et al 2015 ; Dolman et al 2013 ) and providing further evidence to provide healthcare staff with specialised training on PP to enhance their skills and confidence (Dolman et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings reveal contact with healthcare services is inconsistent and can even hinder accessing support, suggesting that NICE guidelines are not being consistently met. This may reflect differences in service provision, including insufficient availability of specialist MBUs which can result in delays receiving appropriate help (Hill et al 2019 ; Jones and Smith 2009 ). It was also found that the needs as a family were often not adequately addressed, echoing work in the broader area of maternal mental health (Megnin-Viggars et al 2015 ; Dolman et al 2013 ) and providing further evidence to provide healthcare staff with specialised training on PP to enhance their skills and confidence (Dolman et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Case study N 5 1 Clozapine Clozapine 200 mg/d was effective within a week. Lutz et al, [45][46][47][48] A systematic review of Doucet published in 2011 on the prevention of PPP has examined the effects of mood stabilizers, APs, and hormone therapy. The treatment option for PPP has included ECT, mood stabilizers, APs, hormones, and the beta blocker propranolol.…”
Section: Participants (N) Treatment Resultsmentioning
confidence: 99%
“…While a small sample, the demographic and service outcome data in this project compares consistently with previously reported data for this setting and other Australian psychiatric MBUs. [6][7][8][9] The observable trend towards increased capacity for urgent admissions over the project period is a key outcome given women with PMHDs preference for MBU admission over general psychiatric wards. 10 A higher proportion of those not admitted experienced perinatal depression and/or anxiety, obsessive compulsive disorder and postpartum situational crises, suggesting a clear role for this model of care.…”
Section: Discussionmentioning
confidence: 99%